대학 신입생의 교양 수업 만족도 유형에 따른 군집화 연구 - 이은준(Lee, Eun-Jun) (교양교육연구, 2017)
이 연구는 교양 수업에서의 교육경험에 대한 학생들의 만족도 유형에 따라 서로 구별되는 군집을 밝혀내고, 군집에 따라 교양 수업 만족도에 영향을 주는 요인에 차이가 있으며, 대학 몰입에 대해서도 차이가 있음을 분석하였다. 연구도구는 한국교육개발원에서 실시한 ‘한국 대학생의 교수·학습과정에 관한 설문조사’이며, 2016년 설문에 참여한 D대학의 1학년 학생 894명의 응답을 분석하였다. 연구결과, 학생들의 만족도 유형은 크게 4개의 군집으로 나타났다. 첫 번째 군집은 ‘만족형 학습자’로 교양 수업 전반에 대해 대체로 만족하고 있다. 두 번째 군집은 ‘비판적 학습자’로 교양 수업에 대해서는 대체로 만족하고 있지만, 수업의 체계적인 구성을 중요하게 생각하고 있으며, 교수자의 수업운영 방식에 대해서도 비판적으로 접근하고 있다. 세 번째 군집은 ‘소극적 학습자’로 교수자의 운영 스타일에 영향을 받는다. 네 번째 군집은 ‘교수자 의존형 학습자’로 편견 없는 표현이나 교수자로부터의 피드백 등 교수자와의 상호작용을 느낄 때 수업에 대한 만족도가 높은 집단이다. 대학 몰입의 측면에서는 두 번째 군집과 네 번째 군집에서 학업중단의사가 높게 나타났다. 교양 수업은 신입생들이 경험하는 대부분의 교수-학습경험이라는 점을 고려할 때 교양 수업의 질적 향상은 곧 신입생들의 대학 몰입과 학업지속의사에 긍정적인 영향을 미친다는 결론에 도달하였다. This study investigated the existence of different subgroups by the pattern of satisfaction to educational experience in liberal arts courses, and identified the differences in factors affecting the degree of satisfaction to the courses by the subgroup. Also it revealed that there were differences in institutional commitment among the groups. The research tool was ‘National Assessment of Student Engagement in Learning’ conducted by Korean Education Development Institute. As a result, there were four different clusters based on the patterns of satisfaction to the liberal arts course. The first group was called ‘satisfied learners’ who were overall satisfied with the most factors of educational experience in the courses. The second group was called ‘critical learners.’ Although they were satisfied with the courses, they considered the importance of systematic organization of the courses. Also they critically approached to the instructors’ method of course management. The third group was called ‘passive learners’ who were affected by the instructors’ styles of teaching. The fourth group was called ‘instructor-dependent learners.’ They tended to be satisfied with when they felt interaction with the instructors’ expression without prejudice and feedback from the instructors. In terms of institutional commitment, the second and the fourth group showed a relatively high degree of intention of college dropout. When we consider that liberal arts courses are most of learning experience during the first year at college, the improvement of liberal arts education may have positive influence on the freshmen’s institutional commitment and the intention of college retention. KCI Citation Count: 3